ANALISA FAKTOR PENENTU KEPUASAN KERJA PERAWAT PELAKSANA DI INSTALASI RAWAT INAP RSUD LANGSA - Dian Ariani; Tarsyad Nugraha; Imam Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
Upgrading and stabilizing the characters of the nurses has recently invented a demand of the society, either in the health services generally or in nursing particularly. Advanced job satisfaction is determined by a standard in which the organization has been implementing behavioral management effectively (4). This research applied the dependent variable that refers to job satisfaction and independent variables that refer to leadership style, motivation, supervision, and work environment. This research applied an analytic survey with a cross-sectional study design. The population of this research required the entire nurses in the Inpatient Room of RSUD Langsa, meanwhile, there were about 73 respondents asan obvious sample of this research and the sampling had applied a technic namely Proportional Stratified Random Sampling. The conclusion of the research stated that leadership style and job satisfaction of the nurses are related to one another in RSUD Langsa with a p-value of 0.001 (p <0.05), there is a correlation between motivation and job satisfaction of the nurses in RSUD LANGA with a p-value of 0,000 (p <0, 05), there is a correlation between supervision and job satisfaction of the nurses in RSUD LANGSA with a p-value of 0,000 (p <0.05) and there is a correlation between the kerha environment and job satisfaction of the nurses in RSUD LANGSA with a p-value of 0.003 (p <0, 05). Based on the multivariate analysis revealed that among the four independent variables that influence the dependent variable (job satisfaction) the most are work motivation and supervision. To the chief of nursing in RSUD LANGSA, to reevaluate to the entire supervisors comprehensively and enhancing supervision towards a standard achievement of working, conducting a cordial relationship with the employees and offering a proper reward in which ensuring the salaries equally should have been attempted to motivate the nurses in working professionally.